A Systematic Literature Review of Crime Prevention Through Environmental Design Principles Against Banks ATM Physical Security Effectiveness (Open International Journal of Informatics, 2021)
Technology development never sleeps, humans creating more high-tech devices for society to use.  Swift movement of technology growth has changed the conceptual design of the physical security control, location landscape, human behaviors factor, and perimeter controls are the factors to determine the security posture of the location. Hence, the rise of the new financial digital banking ecosystem has raised significant new concerns to bank consumers. In order to study the control measurement of current banking industry effectiveness by using the systematic literature review (SLR) to conduct the research that published in the digital library through world wide web. In short, maintaining the principle, policy guideline, and standard framework shall continue review periodically to identify the control measurement effectiveness.